Viability of seed-borne fungi Alternaria alternata, Bipolaris sorokiniana and Drechslera teres in barley seeds in the south of Brazil - Agostinetto,Lenita (2020)
ABSTRACT Some seed-borne fungi can survive in barley seeds; nevertheless, their survival period is unknown in barley seeds under storage conditions in Brazil. The aim of this study was to quantify the viability of the fungi Alternaria alternata, Bipolaris sorokiniana and Drechslera teres in barley seeds stored for 315 days during the off-season in the south region of Brazil. Each cultivar had 400 seeds disinfested and subjected to seed health testing in potato-dextrose-agar (PDA) from December 2011 to September 2012 at 35-day intervals. Data on fungal incidence and viability as a function of the storage time underwent regression analysis. All three fungi were detected in the five cultivars in all evaluated periods, and their incidence and viability significantly reduced with increasing storage periods. Monthly average reduction in the viability of A. alternata was 8%, while that of B. sorokiniana and D. teres was 10%. At the end of the off-season, viability of A. alternata, B. sorokiniana and D. teres, considering the average of cultivars, remained 49.8, 29.6 and 31.0%, respectively.